Criminal Mediation for Minors in Israel - Kandel, Isack (ScientificWorldJournal, 2007)
Mediation was introduced in Canada in 1974 in order to handle a crime of robbery and vandalization committed by adolescents. After mediation, these adolescents agreed to apologize to each of their victims and pay restitution. Several countries (Canada, England, Finland, and the U.S.) have now made this opportunity available in the cases of young offenders. This review describes the process in the south of Israel. We find this method very powerful, but further studies are needed. Due to resource problems, it will not become mainstream in the near future.